Minimal Factionalism in Singapore's People's Action Party. Issue 1 (April 2020) - Tan, Netina
Singapore's People's Action Party (PAP) is one of the longest ruling parties in the world. The PAP's ability to avoid overt factionalism over the years is exceptional, especially compared to the region's personalistic or cadre parties. In recent years, the defection of former PAP cadre Dr. Tan Cheng Bock and the formation of the Progress Singapore Party (PSP) and PM Lee Hsien Loong's family rivalry, which involved PAP elites, have challenged the cohesion of the PAP. This study examines a set of incentives and constraints institutionalised at the party and national levels to foster elite cohesion. It is argued that the critical junctures in the PAP's early years led to the adoption of a cadre party model and a centralised candidate selection process that co-opts like-minded elites into a core that promotes elite unity. Nationally, party switching and factional alignments based on ethnicity or ideology have been systematically banned. Given the lack of credible alternatives that seriously challenge the incumbent PAP, ambitious party cadres would do better toeing the party line and staying loyal.